Capacitation status of frozen thawed Bali bull (80S javanicus) spermatozoa with different heparin concentrations - Sarsaifi, Kazhal; Haron, Abd Wahid; Yusoff, Rosnina; Hani, Homayoun; Yimer, Nurhusien; Naing, Soh Win; Vejayan, Jaya; Othman, Abas Mazni (2012)
The present study was conducted to assess the capacitation status of frozen-thawed Bali spermatozoa in different heparin concentration with a short incubation time. Frozen thawed spermatozoa from Bali bulls were treated with either 25, 50 or 100 ug/ml heparin for 30 min. Capacitation was evaluated by acrosome reaction of spermatozoa and heterologous in vitro fertilization test] fertilization percentage (FP) and fertilization index (FI)]. Acrosome reaction was induced in heparin treated spermatozoa with calcium ionophore A23187 and staining was carried out with naphthol yellow S- erythrosine B to evaluate the response as compared with control (without heparin). Significantly higher percentage of acrosome reaction (AR) spermatozoa was observed after heparin treatment (43.8 - 60.2%) as compared with control (11.6%; p < 0.01). Also, a significantly higher in vitro fertilization rate was recorded in spermatozoa capacitated by 50 and 100 ug/ml heparin (68.4 and 73.6% fertilization percentage, respectively) as compared with control and 25 ug/ml heparin (13.5 and 41% cleavage rate; p < 0.01). It is concluded that Bali spermatozoa capacitated with 50-100 ug/ml heparin had significantly higher ability to improve capacitation status and acrosome reaction.